Hypoglycemia: Updates on Diagnosis and Treatment - Aprilia, Dinda (Fakultas Kedokteran, Universitas Andalas, 2025)
Hypoglycemia is a condition where blood glucose concentration decreases below 70 mg/dL with or without signs or symptoms. Hypoglycemia symptoms may vary from mild to life-threatening conditions, or be classified based on the severity as mild-moderate and severe hypoglycemia. Mortality in patients with severe hypoglycemia was 3 times greater than in patients who experienced mild-moderate hypoglycemia. Management of hypoglycemia is classified based on its severity. Appropriate therapy is needed for hypoglycemia patients because untreated hypoglycemia will reduce the patient's quality of life. Understanding symptoms, prevention, and the management of hypoglycemia is needed, especially in patients who have experienced severe hypoglycemia so that it does not lead to recurrence or fatal condition.